THE USE OF SPEED READING TO IMPROVE FIRST-GRADE STUDENTS AT SMK PUSPA BANGSA BANYUWANGI'S COMPREHENSION OF READING - Nurul Anam; Agus Wijaksono (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2023)
This study examined how SMK Puspa Bangsa Banyuwangi first-graders used speed reading to improve their reading comprehension. This study was conducted in class X-1, which included 40 students, with the help of a writer and an observer. A classroom action research project (CAR) was used to carry out the research. The outcome demonstrated that the students' reading abilities might be improved by using the speed reading strategy. If the teacher has the ability to arrange learning in the classroom by engaging activities proportionately in the teaching process, the use of speed reading techniques might be successful. By providing enough study facilities and infrastructure, a conducive learning environment was maintained. The presence of students' positive responses and their active engagement in each learning activity demonstrated the speed reading technique's effectiveness.